1980
DOI: 10.1111/j.1550-7408.1980.tb05407.x
|View full text |Cite
|
Sign up to set email alerts
|

Thymidylate Synthetase as a Chemotherapeutic Target in the Treatment of Avian Coccidiosis*

Abstract: SYNOPSIS. Thymidylate synthetase (E.C.2.1.1.45) has been demonstrated in unsporulated oocysts of Eimeria tenella. The properties of this enzyme have also been investigated in Tetrahymena pyriformis, as a protozoan model, and 7‐day‐old chick embryo, as a host model. The enzymes from E. tenella and chick embryo were inhibited by all concentrations of MnCl2 and MgCl2 tested. Tetrahymena pyriformis thymidylate synthetase was stimulated by low concentrations of both these cations but was inhibited by high concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1980
1980
1999
1999

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Regeneration of tetrahydrofolate occurs in a reaction catalysed by dihydrofolate reductase (DHFR) 73 with NADPH as the electron donor. TS and DHFR exist as a bifunctional protein in the Trypanosomatidae [277,280], Plasmodium species [281,282] and Eimeria tenella [280,283,284], whereas the enzymes from bacteria, yeast and mammalian cells are distinct and readily separable [285]. It has been reported that Leishmania major promastigotes selected for resistance to the DHFR inhibitor methotrexate or the TS inhibitor 10-propargyl-5,8-dideazofolate overproduce the bifunctional TS-DHFR and show two distinct and uniform amplified regions of DNA [286][287][288][289].…”
Section: Biosynthesis Of Thymine Nucleotidesmentioning
confidence: 99%
“…Regeneration of tetrahydrofolate occurs in a reaction catalysed by dihydrofolate reductase (DHFR) 73 with NADPH as the electron donor. TS and DHFR exist as a bifunctional protein in the Trypanosomatidae [277,280], Plasmodium species [281,282] and Eimeria tenella [280,283,284], whereas the enzymes from bacteria, yeast and mammalian cells are distinct and readily separable [285]. It has been reported that Leishmania major promastigotes selected for resistance to the DHFR inhibitor methotrexate or the TS inhibitor 10-propargyl-5,8-dideazofolate overproduce the bifunctional TS-DHFR and show two distinct and uniform amplified regions of DNA [286][287][288][289].…”
Section: Biosynthesis Of Thymine Nucleotidesmentioning
confidence: 99%
“…This is unfortunate since the oocyst is basically a dormant stage, and the activities of many enzymes of interest would be expected to be low. Thus Wang (1978) was unable to detect thymidylate synthetase in crude extracts of unsporulated oocysts of E. tenella, although we have been able to detect and characterize the enzyme using more sensitive techniques (Coles, Swoboda & Ryley, 1979). Interesting investigations have been carried out on the biochemical basis of sporulation and of catabolic systems operational in the sporozoite, but it is the growing intracellular parasite which is potentially of prime interest.…”
Section: Biochemical Basicsmentioning
confidence: 90%
“…Differences in the enzyme from these sources are reported. Dihydrofolate reductase has been detected in large quantities in the oocysts of E. tenella (Wang, Stotish & Poe, 1975) and thymidylate synthetase has been investigated (Coles, Swoboda & Ryley, 1979). SHMT is the third enzyme of the cycle (Gutteridge & Coombs, 1977) which is shown in Fig.…”
Section: Introductionmentioning
confidence: 99%